Etika dan Tantangan Media dalam Dakwah - Kusnadi; Hawirah Hawirah; Asriadi; Khuzaima; Miftahul Awaliah; Khair khalis (RETORIKA : Jurnal Kajian Komunikasi dan Penyiaran Islam, 2026)
The development of information and communication technology has brought significant changes in the method of preaching. Mass and digital media have become strategic means in spreading preaching messages to the wider community. However, the use of media also presents complex ethical challenges. This article discusses the ethics of using media in preaching activities and the challenges faced by preachers in the digital era. The method used is a literature study with a descriptive qualitative approach. The results of the study show that preaching through the media must pay attention to the principles of communication ethics, such as honesty, responsibility, and respect for the audience. The main challenges faced include the spread of hoaxes, provocative content, commercialization of preaching, and the decline in digital literacy among the community. Therefore, there needs to be an integration between Islamic ethical values and an understanding of technology in today's preaching strategy.